All Days 1987
DOI: 10.2118/16395-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Solution for Unsteady Liquid Flow in a Reservoir With a Uniformly Fractured Zone Around the Well

Abstract: An analytical model is presented which describes the pressure behaviour of a well completed in a reservoir wherein natural fractures occur over a limited area around the wellbore. The flow in the reservoir is treated as a composite reservoir flow problem, the region adjacent to the wellbore being considered as a fractured medium and the outer region as an homogeneous one. Wellbore storage and skin effects are included in the solution, and the flow in the fractured region is mathematically described by Warren a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…en, a radial discontinuity of physical properties occurs around the wellbore, and the reservoir can be divided into two zones: fracture closure zone (inner zone) and unclosed fracture zone (outer zone). us, the idea of composite reservoir can be used to deal with stress sensitivity and fracture closure appeared in fractured reservoirs [21][22][23]. Figure 1 is a schematic illustration of a vertical well with fracture closure near the wellbore in a fractured reservoir.…”
Section: Physical Model Of Vertical Well In Fracturedmentioning
confidence: 99%
“…en, a radial discontinuity of physical properties occurs around the wellbore, and the reservoir can be divided into two zones: fracture closure zone (inner zone) and unclosed fracture zone (outer zone). us, the idea of composite reservoir can be used to deal with stress sensitivity and fracture closure appeared in fractured reservoirs [21][22][23]. Figure 1 is a schematic illustration of a vertical well with fracture closure near the wellbore in a fractured reservoir.…”
Section: Physical Model Of Vertical Well In Fracturedmentioning
confidence: 99%
“…Sci. 2019, 9, Although Prado and Da [10] mainly aimed at analyzing transient pressure, the dimensionless production rate solution can also be obtained based on the relationship of Equation (14). Therefore, we consider the circumstance of hw = h in our model, which means the well is penetrated completely.…”
Section: Model Verificationmentioning
confidence: 99%
“…Two decades later, Olarewaju and Lee [8,9] proposed an analytical solution to analyze pressure transient behavior for wells in finite composite reservoir system. Besides the composite formation with single porosity media in inner and outer regions, many researchers [10][11][12][13][14] also developed the mathematical model for composite dual-porosity reservoirs. Subsequently, Kuchuk and Habashy [15] solved fluid flow problems in composite reservoirs by reflection and transmission theory of electromagnetics.…”
Section: Introductionmentioning
confidence: 99%
“…Prado and Da Prat, 1987, presented a mathematical model for homogenous systems with hydraulically fractured vertical wells. They concluded that no general type curves could be generated for this system due to presence of a large number of controlling parameters in this system.…”
Section: Introductionmentioning
confidence: 99%